CSR disclosures in buyer-seller markets: The impact of assurance of CSR disclosures and incentives for CSR investments - De Meyst, Karen J.; Cardinaels, Eddy; Van den Abbeele, Alexandra (Accounting, Organizations and Society, 2024)
This study examines how buyers and sellers react to CSR disclosures in competitive experimental markets. We examine the impact of two important policy interventions: whether assurance of CSR disclosures is present or not and whether sellers receive incentives to invest in CSR. Sellers, as preparers of the disclosures, reveal their levels of CSR investments (proxied by corporate giving), in addition to setting selling prices. These disclosures can be inaccurate. Buyers, as users of the disclosures, choose to do business with a seller and might do so for reasons beyond established prices (e.g., buy from sellers that invest more in CSR). The results of our market experiment show that assurance leads sellers to more accurately disclose their CSR investments. We further predict and find that the assurance of CSR disclosures affects economic outcomes (i.e., CSR investments and prices paid) in particular when sellers receive incentives to invest in CSR compared to when incentives are absent, because incentives can raise expectations among market participants that CSR is important. Results of an additional M-Turk experiment provide corroborating evidence that the use of sustainability incentives does raise social expectations among market participants with regard to CSR investments. We add new insights to the literature on economic effects of CSR reporting and the partner selection literature by showing when and how policy interventions can increase the impact of CSR disclosures.